Improving Ability Of Grade XI Students In Reading At Madrasah Aliyah Negeri Kota Banjarbaru By Using SQ3R Tecnique - Ridhani Fizi (LP2M IAI Darussalam Martapura, 2023)
Abstract This study is categorized as a classroom action research (CAR). This study proposed teaching reading by using SQ3R tecnique as the strategy in the teaching English at the second grade students of MAN Kota Banjarbaru to solve the students’ incompetency on reading skill. As the result of the preliminary study indicated that the students’ problems toward their reading competence was students could not comprehend the text. Their literal and inferential reading skills were low. It seems that they did not know the details passage on which main ideas, cause and effect relationship are built. In comprehending the explicit information, the students could not locate the details. They just focused on understanding the meaning of sentences. As the result they got difficulty in answering the comprehension questions. Moreover, the students could not make inferences that were implied in the text. They could not understand the text and merely took the last paragraph as a conclusion of the paragraph. Therefore, the criteria of success were directed to the mentioned problems. The results showed that by using SQ3R tecnique, the students’ reading comprehension achievement and the students’ participation in the classroom were improved highly positive. Keywords: SQ3R, improve, reading comprehension achievement